Direct H-2-to-H2O2 oxidation over highly active/selective Br-F-Pd/Al2O3 catalyst in aqueous acidic medium: Influence of process conditions on the H2O2 formation - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2009)
The influence of the O-2/H-2 mote ratio in the gaseous feed and also those of other reaction conditions [viz. concentration of H3PO4 (0-5 mol/dm(3)). temperature (5-50 degrees C, gas (H-2 and O-2) space velocity (5.8-23.4 h(-1)) and reaction time (0.1-8 h)] on the H2O2 formation in the H-2-to-H2O2 oxidation over the Br(1 wt%)-F(1 wt%)-Pd(5 wt%)/Al2O3 catalyst in an aqueous acidic (H3PO4) medium have been thoroughly investigated. The effects of the O-2/H-2 ratio, reaction temperature and acid concentration on the destruction of H2O2 by its decomposition and/or hydrogenation reactions over the catalyst in the acidic reaction medium have also been studied. The net H2O2 formation (H2O2 yield) over the catalyst passed through a maximum with increasing the acid concentration, the temperature or the O-2/H-2 feed ratio. However, it decreased markedly with increasing the gas space velocity or the reaction period. The H2O2 decomposition and hydrogenation activities of the catalyst increased appreciably with increasing the reaction temperature and decreased with increasing the acid concentration. The H2O2 destruction during the H-2-to-H2O2 oxidation increased with increasing the concentration of H-2 (relative to that of O-2) due to the increased H2O2 hydrogenation rate over the catalyst. The net H2O2 formation in the H-2-to-H2O2 oxidation decreased sharply with increasing the initial amount of H2O2 present in the reaction mixture. The presence of H2O2 and the higher H-2/O-2 ratios have detrimental effects on the net formation of H2O2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Br-F-Pd/Al2O3 catalyst; H2O2 decomposition; H2O2 hydrogenation; hydrogen oxidation; Hydrogen peroxide